Ultrasonic supported dye removal by a novel biomass - Gulen, Jale; Kucuk, Ilknur; Yalcin, Berrin Saygi; Celik, Selen Ezgi; Ozgur, Mahmure (WALTER DE GRUYTER GMBH, 2022)
Sumac Leaves (Rhus Coriaria L), were used as a possible adsorbent of Basic Blue 3 (BB3) removal. The main affecting parameters on adsorption such as concentration, pH and temperature were investigated. Adsorption equilibrium was reached in 30 min. The ultrasonic effect was also enhanced the dyestuff removal. Adsorption capacity was rised from 0.566 to 1.826 mg/g, as rising the concentration from 4 mu g/mL to 10 mu g/mL. Several isotherm models including Langmuir, Freundlich and Temkin were applied for explaining the adsorption mechanism. Temkin and Langmuir isotherm models describe the system well. Pseudo first order, pseudo second order and intra particle kinetics were evaluated. Pseudo second order diffusion model supports the adsoprption and also intra particle diffusion plays an important role for BB3 removal. Thermodynamics of the adsorption were commented. -2219.5 J/mol of Gibbs energy showed us a spontaneous and physical adsorption.
Keywords: BB3; biomass; ultrasonic effect; uptake; LOW-COST ADSORBENT; METHYLENE-BLUE ADSORPTION; FIXED-BED ADSORPTION; ACTIVATED CARBON; AQUEOUS-SOLUTION; BASIC DYE; WASTE-WATER; FLY-ASH; EQUILIBRIUM; KINETICS; Chemistry